TINGKAT KECEMASAN PREOPERATIF PADA PASIEN YANG AKAN MENJALANI TINDAKAN ANASTESI PADA OPERASI ELEKTIF - VALLEN TAMARA SPRECKHELSEN; MUHAMMAD JALALUDDIN ASSYUTHI CHALIL (JURNAL ILMIAH KOHESI, 2021)
Based on the studies that is conducted in Canada, Sri Lanka, Saudi arabia regarding the level of preoperatif anxiety, itsappears that the overal prevalence of preoperative is very high. Low preoperative anxiety level are expected towards anykind of dangerous situation or life thretening situstion, especially for patient that is never been through surgery before.To determine the level of preoperartif anxiety patient that will do anasthetic procedures. Preoperative patient anxiety is apervasive problem that can have far-reaching effects. Among the effects of these effects are increased postoperative pain,increased risk of infection and longer healing time. Many factors influence preoperative patient anxiety, including the need forsurgery, loss of perception of control, fear of postoperative pain, and body image changes. According to Wawan Rismawanet al., 2019 the level of anxiety in preoperative patients at the Dr. Soekardjo Hospital, Tasikmalaya City was mostly anxious,was 21 people (50%). All preoperative patients at dr sokardjo Hospital have never been given hypnotherapy to treat anxiety.Preoperative anxiety is common and the reported prevalence of preoperative anxiety among patients undergoing varioustypes of surgery was found to be as high as 60% to 90%. It has been reported that in hospitalized patients for nonsurgicalreasons 10% to 30% experience anxiety, this anxiety incidence can increase to 60% to 80% in patients waiting for surgeryand 5% of patients who are anxious before undergoing surgery.